1982
DOI: 10.1038/bjc.1982.220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the effects of tranexamic acid and urokinase on metastasis of Lewis lung carcinoma

Abstract: Summary.-Lewis lung carcinoma cells were implanted in the foot-pads of mice and the effects of the plasminogen-plasmin inhibitor tranexamic acid (t-AMCHA) and of the plasminogen activator urokinase on metastasis were examined by electron microscopy. The intravascular tumour cells were not associated with thrombus formation in either control or urokinase -treated mice. Polymerized fibrin deposition around tumour cells and thrombi composed of fibrin and platelets was observed only in the mice given t-AMCHA. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…As a result of rapid tumor growth in the lungs, the host animals died of bleeding in the pleural cavity within 3 weeks after tumor cell inoculation. 21,22,24,25) In the present experiment, mice were i.v. administered either a single dose or intermittent doses (every 7th day for a total of 4 doses, q7d×4) of DE-310, once daily times 5 doses (qd×5) of DX-8951f, or a single dose of CPA beginning on day 8.…”
Section: Compoundsmentioning
confidence: 90%
See 1 more Smart Citation
“…As a result of rapid tumor growth in the lungs, the host animals died of bleeding in the pleural cavity within 3 weeks after tumor cell inoculation. 21,22,24,25) In the present experiment, mice were i.v. administered either a single dose or intermittent doses (every 7th day for a total of 4 doses, q7d×4) of DE-310, once daily times 5 doses (qd×5) of DX-8951f, or a single dose of CPA beginning on day 8.…”
Section: Compoundsmentioning
confidence: 90%
“…Meth A was obtained from Hokkaido University, Sapporo. M5076 20) and 3LL 21,22) were obtained from the Japanese Foundation for Cancer Research, Tokyo. Meth A and M5076 were maintained by serial intraperitoneal passage in syngeneic mice.…”
Section: Compoundsmentioning
confidence: 99%
“…34) In some cases of lung cancer, the prognosis of patients with high expression of u-PA is reported to be significantly worse than that of patients with lower expression of u-PA. 35) Lymphatic metastasis of lung cancer is correlated with enhanced expression of u-PA. 36,37) It has been reported that the invasion and metastasis of LLC cells were inhibited by blocking the u-PA/ plasminogen system. [28][29][30] In addition, the c-Jun proto-oncogene product, which is a component of transcription factor AP-1, is also overexpressed in lung cancer patients with metastasis. 38,39) AP-1 is a major transcriptional enhancer for the transactivation of u-PA and u-PAR genes, expression of which is dependent on the activation of AP-1, although another factor, PEA3, binds to their promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…4). Because blocking of the u-PA/plasminogen system is able to inhibit LLC cell invasion, [28][29][30] we next examined the effect of TAC-101 on the production of u-PA. As shown in Fig. 5A, two fibrinolytic bands were detected at approximately 100 kDa and at 55 kDa in the zymogram.…”
Section: )mentioning
confidence: 99%
“…Next, plasminogen is converted to active plasmin in a reaction that is catalyzed by PA (uPA or tPA) (11). It has been reported that the proteolytic activity of plasmin contributes to angiogenesis (1, 12) and invasion/metastasis (13)(14)(15). Reports also suggest that the morbidity and mortality of mice with Lewis lung carcinoma are due to excessive plasmin generation (16).…”
mentioning
confidence: 99%